Courting white southerners: Theodore Roosevelt's quest for the heart of the South. Issue 1 (2nd January 2019) - Burns, Adam
ABSTRACT: Most studies of President Theodore Roosevelt address his "southern strategy" to revive the Republican Party's fortunes in a region where it was effectively shut out by 1900. This essay revisits Roosevelt's approach to the South between 1901 and 1912 and argues that wooing white southerners away from the Democratic Party, more than any other approach, represented Roosevelt's overriding strategy for the revitalization of the southern GOP.